Child maltreatment and substance-use-related negative consequences: Longitudinal trajectories from early to mid adolescence. (July 2020) - Hagborg, Johan Melander; Thorvaldsson, Valgeir; Fahlke, Claudia
Highlights: Child maltreatment is associated with higher levels of substance use related negative consequences (SURNCs). Maltreated adolescents use more alcohol and substances compared to their peers. Alcohol and substance use partly mediate the relationship between maltreatment and SURNCs. Abstract: Background: Child maltreatment is associated with adult substance use disorders (i.e. alcohol and/or illicit drug use). Little is known about the behavioral pathways characterizing adolescent substance users who were subjected to childhood maltreatment. Here, we investigate the longitudinal trajectories of substance-use–related negative consequences (SURNCs) in adolescence in relation to childhood maltreatment. Method: We drew the data (N = 1515) from the longitudinal multidisciplinary research program LoRDIA (Longitudinal Research on Development In Adolescence), of which 406 reported substance use and were included in the presented analyses. The data were collected via self-report questionnaires in classroom settings at three time points (mean age: 13.5, 14.4 and 15.0). We obtained information for childhood maltreatment using the Childhood Trauma Questionnaire-Short Form (CTQ-SF) and data of frequencies of SURNC with a questionnaire scale. Results: Estimates from zero-inflated Poisson growth curve model revealed no baseline differences in SURNCs across children reporting none, single, or multiple maltreatment before the age of twelve. However, children experiencing multiple maltreatment displayed a greater increase in the frequency of SURNCs during the transition from early to mid adolescence than did those reporting no maltreatment. These estimates were only partly influenced by the inclusion of frequency of alcohol and substance drug use to the model. Conclusions: These findings imply that children suffering maltreatment are at a higher risk of experiencing SURNCs, a factor known to elevate the risk of substance use disorders later in life, as they transition from early to mid adolescence.